Peran Guru dalam Pemanfaatan Media Pembelajaran Berbasis Teknologi Informasi dan Komunikasi di Sekolah Dasar - Winanda Amilia (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
The advantage of instructional media based on Information and Communication Technology (ICT) is that it can help learning activities. The learning activities that utilize ICT-based instructional media can support the success of learning objectives. This study aims to determine the role of teachers in utilizing learning media that uses ICT in elementary schools. This is related to the problem of developing teacher competence in the use of ICT in learning. To obtain research data used survey research methods. Data were obtained from teachers at the 13 Pasar Remaja Elementary School, Lembah Segar District, Sawahlunto City, West Sumatra. The data was collected using a questionnaire and the research data were analyzed using the percentage technique. The results of this study pointed out that 53.3% of teachers at the Sawahlunto City Elementary School realize the importance of ICT-based instructional media but have not utilized them optimally because they are constrained by skills in the field of ICT.